Implementasi maqamat al-taqwa, al-tawakkal dan al-ridla dalam kehidupan modern - NURACHSANA, MAULIDIAH (Maliki Interdisciplinary Journal, 2025)
The application of the values of maqamat such as taqwa, tawakkal, and ridha in contemporary life plays an important role in shaping the character and morals of individuals. These three values are key elements of Sufi teachings that can help individuals face various challenges in an increasingly complex era.Taqwa refers to an individual’s awareness and obedience to Allah, which is reflected in their attitudes and behavior. In a modern context, taqwa is not limited to the performance of ritual worship but also includes positive social actions, such as maintaining a relationship with Allah through the implementation of His commands and avoiding His prohibitions.Tawakkal is the attitude of surrendering to Allah after making every possible effort. In modern life, tawakkal can be manifested through hard work and diligent effort. While tawakkal teaches us to submit, effort remains an essential component in achieving goals. Ridha, or contentment, is the acceptance of Allah’s decrees with a sincere heart. In the context of modern life, ridha can be applied by accepting all outcomes of our efforts, whether success or failure, as part of Allah’s plan.Thus, the application of the values of maqamat taqwa, tawakkal, and ridha in modern life is highly relevant for building strong character and good morals. By integrating these three values, individuals can not only better face the challenges of their times but also contribute positively to society.